Usability tests on bioinformatics mobile applications - Falgueras-Cano, Juan (My University, 2014)
Mobile devices are experiencing a dramatic increased use among clinicians and researchers. Current bio-apps are not mature enough for a serious bioinformatic use. We are addressing the key aspects that these particular interfaces and situations present to the user. In doing so, we have develop an ambitious framework for an open list of services easy and friendly accesible able to give useful results on the mobile
International Congress Poster, supported by MrSymBioMath IAPP project (Code: 324554) Marie Curie Project
Keywords: Bioinformática